Quantcast algebra question?? - XP Math - Forums
XP Math Home Sign Up FREE! | Sign In | Classroom Setup | Common Core Alignment PDF Version

Go Back   XP Math - Forums > Welcome > Off-Topic Discussion

Reply
 
Thread Tools Display Modes
Old 08-01-2007   #1
gudgurl87
Guest
 
Posts: n/a
Default algebra question??

Solve by factoring and using the principle of zero products: (7z+9) (z+7) = 47 and then it asks for the solutions...any help would be appreciated thanks!thanks guys i get it now!
  Reply With Quote
Old 08-01-2007   #2
Andrew J
Guest
 
Posts: n/a
Default

Foil the factors out and set=0When you factor the trinomial, you will get 2 factors. (7z+16) and (z+1), set them=0two solutions-------> z= -16/7 and z= -1
  Reply With Quote
Old 08-01-2007   #3
mahl2392
Guest
 
Posts: n/a
Default

Simplifying(7z + 9)(z + 7) = 47Reorder the terms9 + 7z)(z + 7) = 47Reorder the terms9 + 7z)(7 + z) = 47Multiply (9 + 7z) * (7 + z)(9(7 + z) + 7z * (7 + z)) = 47((7 * 9 + z * 9) + 7z * (7 + z)) = 47((63 + 9z) + 7z * (7 + z)) = 47(63 + 9z + (7 * 7z + z * 7z)) = 47(63 + 9z + (49z + 7z2)) = 47Combine like terms: 9z + 49z = 58z(63 + 58z + 7z2) = 47Solving63 + 58z + 7z2 = 47Solving for variable 'z'.Reorder the terms:63 + -47 + 58z + 7z2 = 47 + -47Combine like terms: 63 + -47 = 1616 + 58z + 7z2 = 47 + -47Combine like terms: 47 + -47 = 016 + 58z + 7z2 = 0Factor a trinomial.(8 + z)(2 + 7z) = 0Subproblem 1Set the factor '(8 + z)' equal to zero and attempt to solve:Simplifying8 + z = 0Solving8 + z = 0Move all terms containing z to the left, all other terms to the right.Add '-8' to each side of the equation.8 + -8 + z = 0 + -8Combine like terms: 8 + -8 = 00 + z = 0 + -8z = 0 + -8Combine like terms: 0 + -8 = -8z = -8Simplifyingz = -8Subproblem 2Set the factor '(2 + 7z)' equal to zero and attempt to solve:Simplifying2 + 7z = 0Solving2 + 7z = 0Move all terms containing z to the left, all other terms to the right.Add '-2' to each side of the equation.2 + -2 + 7z = 0 + -2Combine like terms: 2 + -2 = 00 + 7z = 0 + -27z = 0 + -2Combine like terms: 0 + -2 = -27z = -2Divide each side by '7'.z = -0.2857142857Simplifyingz = -0.2857142857Solutionz = {-8, -0.2857142857}
  Reply With Quote
Old 08-01-2007   #4
stuart b
Guest
 
Posts: n/a
Default

expand7z^2 + 49z +9z +63 = 477z^2 + 58z + 16 = 0(7z + 2)(z + 8) = 0answers; -2/7 , -8
  Reply With Quote
Reply

Thread Tools
Display Modes

Posting Rules
You may not post new threads
You may not post replies
You may not post attachments
You may not edit your posts

BB code is On
Smilies are On
[IMG] code is On
HTML code is Off

Forum Jump


All times are GMT -4. The time now is 12:02 PM.


Powered by vBulletin® Version 3.8.11
Copyright ©2000 - 2020, vBulletin Solutions Inc.
XP Math